PENDIDIKAN ANTI-BULLYING SEBAGAI UPAYA MENCIPTAKAN LINGKUNGAN BELAJAR YANG AMAN DAN INKLUSIF: KAJIAN PUSTAKA TEORITIS DAN PRAKTIS - Rusiadi, Rusiadi; Rosdiana Mata (Prosiding Seminar Nasional Indonesia, 2025)
Bullying in schools is a serious problem that has a negative impact on students' psychological, social, and academic development. Anti-bullying education is a strategic effort to prevent and combat bullying, while fostering a safe, friendly, and inclusive school culture. This study uses a library research approach, examining theoretical and practical literature related to anti-bullying education. From a theoretical perspective, various scientific frameworks—such as Bronfenbrenner's ecological theory, Maslow's theory of needs, Kohlberg's moral theory, and the concept of school climate—show that a sense of security is a fundamental need to support optimal learning. Meanwhile, from a practical perspective, the implementation of anti-bullying education involves school policies, teacher training, student involvement, parental support, counselling services, and the strengthening of digital literacy. This study concludes that anti-bullying education is not only a means of preventing violent behaviour, but also an important instrument in realising inclusive, humanistic, and democratic schools.